First report and molecular analysis of population stability of the invasive Gulf wedge clam, Rangia cuneata (G.B. Sowerby I, 1832) in the Pomerian Bay (Southern Baltic Sea) - R. Panicz; P. Eljasik; K. Wrzecionkowski; N. Śmietana; M. Biernaczyk (The European Zoological Journal, 2022)
Native to the Gulf of Mexico, Gulf wedge clam (Rangia cuneata) has been successfully invading Baltic Sea since first introduction with ballast waters in 2010. In this study, we report new occurrence sites in the Pomeranian Bay and in the brackish water of the Szczecin Lagoon. We aimed to describe the structure and stability of the new population of Gulf wedge clam using ecological indicators (i.e. condition index, length-at-age) and a molecular approach targeting first cytochrome oxidase subunit (COX1) fragments. The study showed an age structure dominated by adult clams (aged 4+), rather than the often reported juveniles. We found that the condition of the R. cuneata population in the Pomeranian Bay is characteristic of the expansion model after bottleneck. Genetic analyses indicated low nucleotide (π = 0.00387 ± 0.00012) and haplotype (h = 0.79 ± 0.018) diversity. A haplotype network inferred by a median-joining method showed lack of haplotype H6 (Chesapeake Bay, NW Atlantic) and numerous individuals with haplotype H1 (Gulf of Mexico). Demographic parameters (non-significant Tajima’s D = 2.058, Fu’s Fs = 2.298, Fu and Li’s D* = 1.195, and significant Fu and Li’s F test = 1.757) suggested that the population underwent a moderate population bottleneck, while analysis of mismatch distribution showed a bimodal shape which may imply population admixture as a consequence of “allelic surfing”. Moreover, we concluded that R. cuneata has successfully invaded the basin of the LNG terminal, although our study proved non-linear growth of this species.